Confronting the Crisis: A University Searches for Relevance - Abinales, P.N. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Nation in Crisis: A University Inquires into the Present; Proceedings of the First Part of the University of the Philippines colloquium of the State of the Nation . Edited by Alexander R. Magno, University of the Philippines, 1984. 251 pages.
Keywords: University of the Philippines; State of the Nation